Analysis of bone density of the edentulous jaws using cone-beam computer tomography images - Strohonova, T. V.; Varzhapetian, S. D.; Varzhapetian, A. S.; Строгонова, Тетяна Василівна; Варжапетян, Сурен Діасович; Варжапетян, Арсен Суренонович (My University, 2024)
Aim:To study the existence of a relationship between the density of bone tissue and the length of the edentulous part of the tooth row.
Keywords: тези доповідей